59 Perspectives of deprescribing experts on opioid overtreatment in australia: a focus group study. (4th December 2019) - Schneider, Carl; Langford, Aili; Lin, Christine; Penm, Jonathan; Blyth, Fiona; Bero, Lisa; Gnjidic, Danijela
Abstract : Objectives: Misuse and abuse of opioids is a major international public health problem leading to harms including increased risk of hospitalization, morbidity and death. Overtreatment with opioids contributes to misuse and has been documented in the USA, Australia and other countries. In order for health professionals to manage opioid overtreatment, guidance on when and how to deprescribe or reduce opioids is required. A key step for guideline development is to understand the perspectives of stakeholders. The aim of this study was to explore the perspectives of Australian deprescribing experts regarding opioid deprescribing practices. Method: A purposive sample of deprescribing experts (including prescribers, pharmacists, researchers and policymakers) were identified for recruitment at the 2018 Australian Deprescribing Network annual meeting. Focus groups were conducted, audio recorded, transcribed verbatim, and entered into QSR NVivo 11 for coding.Inductive thematic analysis using a phenomenological perspective was completed, following the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Results: Two focus groups (n= 20 participants) were conducted in December, 2018. A central theme identified in the focus groups was that opioid deprescribing was considered more challenging than deprescribing of other medicines due to additional user and prescriber-level barriers, including barriers at the organizational and system levels. Addiction was seen as a key barrier due to the intrinsic properties of opioids and that opioid users may be using opioids other than for physical analgesia. Prescribers were perceived to be hesitant to initiate deprescribing due to concerns of user resistance, potentially affecting the therapeutic relationship. This is of concern as medicines of high addictive potential may result in reduced user desire to request cessation. The opioid deprescribing process is considered a time-intensive activity without system-level incentives or clear guidance. Desirable elements for opioid deprescribing guidelines were consideration of psychosocial factors including; opioid phobia, stigma, shared decision making and vulnerable patient populations. Although specialist multidisciplinary care was seen as an enabler, accessibility was poor due to lengthy wait times for referral. Potential strategies to reduce opioid overtreatment could include patient education on the nature of pain and alternatives to opioids as well as targeting routine opioid prescribing in the acute care setting due overdiagnosis of anticipated pain as well as lack of planning of opioid tapering or cessation. Conclusions: Opioid deprescribing was perceived by deprescribing experts as a complex, challenging practice with continued overtreatment the default behavior for both prescribers and opioid users. Consequently, prescribers are hesitant to initiate deprescribing activity. Efforts to reduce opioid overtreatment would require development of guidelines with the inclusion of psychosocial factors with a multi-target, multi-modal intervention strategy that incorporates behavioral change techniques.